Myeloid Takl Acts as a Negative Regulator of the LPS Response and Mediates Resistance to Endotoxemia - Eftychi, Christina; Karagianni, Niki; Alexiou, Maria; Apostolaki, Maria; Kollias, George (PLOS ONE, 2012)
TGFβ-activated kinase 1 (TAK1), a member of the mitogen-activated protein kinase kinase kinase (MAP3K) family, is considered a key intermediate in a multitude of innate immune signaling pathways. Yet, the specific role of TAK1 in the myeloid compartment during inflammatory challenges has not been revealed. To address this question, we generated myeloid-specific kinase-dead TAK1 mutant mice. TAK1 deficiency in macrophages results in impaired NF-κB and JNK activation upon stimulation with lipopolysaccharide (LPS). Moreover, TAK1-deficient macrophages and neutrophils show an enhanced inflammatory cytokine profile in response to LPS stimulation. Myeloid-specific TAK1 deficiency in mice leads to increased levels of circulating IL-1β, TNF and reduced IL-10 after LPS challenge and sensitizes them to LPS-induced endotoxemia. These results highlight an antiinflammatory role for myeloid TAK1, which is essential for balanced innate immune responses and host survival during endotoxemia.